A study into the association between local recurrence rates and surgical resection margins in organ‐sparing surgery for penile squamous cell cancer. (27th April 2018) - Sri, Denosshan; Sujenthiran, Arunan; Lam, Wayne; Minter, Janice; Tinwell, Brendan E.; Corbishley, Catherine M.; Yap, Tet; Sharma, Davendra M.; Ayres, Benjamin E.; Watkin, Nick W.
Abstract : Objective: To evaluate the significance of close surgical margins in organ‐sparing surgery (OSS) in the treatment of penile squamous cell carcinoma (pSCC) and clinicopathological factors that may influence local recurrence. Patients and Methods: At our tertiary referral centre, between March 2001 and September 2012, 332 patients treated with OSS for pSCC had clear surgical margins. As the focus was the impact of close clear margins on local recurrence, patients with positive margins were excluded for the purpose of this study. Our overall positive margin rate for OSS in penile cancer is 7.6% (42 patients). Analysis was carried out on an on‐going prospective database, including prospective accurate pathological recording of surgical margins. Patients underwent OSS after multidisciplinary team (MDT) discussion. Local recurrence was the primary outcome measured and Fisher's exact test and time‐to‐recurrence curves were used in the analysis. All local recurrences were scrutinised by the MDT and were categorised into: true recurrences or metachronous new occurrences (i.e. tumours arising from a background of penile intraepithelial neoplasia and forming on an epithelial surface not related to the site of initial resection). A multivariate analysis was also conducted to elucidate other factors influencing local recurrence. Results: In all, 64% of the patients had a <5 mm clear deep surgical margin, with 16% clear by <1 mm. Overall, 4% of patients had a true local recurrence, with a median time to recurrence of 6 months. In all, 53% were due to embolic spread, with residual occult local disease accounting for 47%. There was a statistically significant relationship between cavernosal involvement ( P = 0.014) and lymphovascular invasion (LVI; P = 0.001) and local recurrence. Although multivariate analysis revealed that the extent of clear margin was not a predictor of disease ( P = 0.405), we found an increased risk of local recurrence in the clear margin cohort of <1 mm compared to those of >1 mm ( P < 0.001). Those patients considered to have metachronous tumours were scrutinised by our MDT, and eight patients (2.4%) were found to have new occurrences. Our overall proportion of patients therefore needing further treatment for either new occurrences or recurrent disease after OSS stands at 6.4%. Conclusions: Overall the presence of local recurrent disease in OSS in our experience is low (4%). We report an embolic mechanism of local recurrence, strongly suggested by the presence of cavernosal involvement and LVI. We conclude that a deep clear margin of >1 mm has a very low risk of local recurrence in penile OSS.